So dijakinje uspešnejše od dijakov? - Štraus, Mojca (Sodobna pedagogika, 2009)
This article compares the performance of female students with the performance of male students in upper-secondary education. In the last several decades, there has been an increasing interest in gender differences in education with regard to achievement in different areas and at different levels of education, as well as with regard to other comparisons such as attitudes towards science, in Programme of International Student Assessment (PISA) 2006. Evidence-based decision making in education and the consideration of possible inequealities between genders are necessary for improvement of the quality of education for all students. Using the PISA 2006 database enables investigation of the reading, mathematics and science achievements of Slovenian students at the beginning of upper-secondary education. We show that findings about gender differences at the general level of the overall population of 15 year olds change considerably when gender differences are studied within individual educational programmes. A possible explanation for this seeming contradiction was found in gender variability among students enrolled in individual educational programmes and in the finding that larger proportions of high-achieving male students in comparison to their high-achieving female peers enter other educational programmes in addition to general and classical upper-secondary programmes.
Keywords: vzgoja in izobraževanje; pismenost; literacy; PISA; razlike med spoloma; dijaki; dijakinje; raziskave